2019
DOI: 10.1002/hed.26018
|View full text |Cite
|
Sign up to set email alerts
|

Potential pitfalls in incorporating plasma Epstein‐Barr virus DNA in the management of nasopharyngeal carcinoma

Abstract: Background: This study identifies potential pitfalls in incorporating plasma Epstein-Barr virus (EBV) DNA into the management of nasopharyngeal carcinoma (NPC).Methods: A total of 208 NPC patients without distant metastasis who received radical treatment and had measurements of EBV DNA at baseline, 8 weeks and 26 weeks postradiotherapy were analyzed. Prognostic and predictive values at each time-point were compared.Results: Risk stratification by pretreatment level failed to identify a poor prognostic group. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Additionally, post-radiotherapy EBV DNA levels in the plasma of patients with NPC predicted locoregional failure, distant metastasis, and death ( 20 ). Post-treatment plasma EBV DNA levels also predicted distant metastasis ( 21 ) and tumor recurrence ( 22 ); thus, additional treatment in patients with high post-treatment EBV DNA levels may prevent relapse ( 14 ). Many NPC prognostic models are based on the EBV characteristics and serological indicators ( 19 , 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, post-radiotherapy EBV DNA levels in the plasma of patients with NPC predicted locoregional failure, distant metastasis, and death ( 20 ). Post-treatment plasma EBV DNA levels also predicted distant metastasis ( 21 ) and tumor recurrence ( 22 ); thus, additional treatment in patients with high post-treatment EBV DNA levels may prevent relapse ( 14 ). Many NPC prognostic models are based on the EBV characteristics and serological indicators ( 19 , 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that EBV-DNA levels in advanced stage NPC are signi cantly higher than those in stage I and II NPC [31][32][33]. Du et al observed that the level of EBV-DNA was correlated with age,…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, relatively common in Southeast Asian countries, and in endemic regions of China, it reaches an incidence of around 20/100,000 2 . Epstein-Barr Virus (EBV) infection is an etiologic factor in the development of endemic, nonkeratinizing (World Health Organization type II/III) NPC, 3 and plasma EBV-DNA levels at different time points in treatment have been correlated with prognostic endpoints, including distant metastasis, locoregional recurrence, and death 4–14 . Prognostic models using EBV-DNA levels have been devised to supplement TNM staging, and EBV-DNA levels are used in some institutions to monitor disease recurrence during posttreatment surveillance 4,15 .…”
mentioning
confidence: 99%
“…2 Epstein-Barr Virus (EBV) infection is an etiologic factor in the development of endemic, nonkeratinizing (World Health Organization type II/III) NPC, 3 and plasma EBV-DNA levels at different time points in treatment have been correlated with prognostic endpoints, including distant metastasis, locoregional recurrence, and death. [4][5][6][7][8][9][10][11][12][13][14] Prognostic models using EBV-DNA levels have been devised to supplement TNM staging, and EBV-DNA levels are used in some institutions to monitor disease recurrence during posttreatment surveillance. 4,15 The role of EBV-DNA in NPC is an area of extensive research, with scores, if not hundreds, of publications on the subject in the last 20 years.In the current issue of The Cancer Journal, He and colleagues report on the prognostic value of EBV-DNA levels before, after, and in long-term follow-up after treatment for NPC.…”
mentioning
confidence: 99%